PERAN BIMBINGAN PRANIKAH DALAM MEWUJUDKAN KEHARMONISAN KELUARGA DI GEREJA BETHEL INDONESIA TABGHA BATAM - Tahan Sitanggang (JURNAL IMPARTA, 2023)
Many efforts have been made to form a strong commitment when undergoing family relationships, to achieve true harmony, the role of premarital guidance in realizing family harmony has a special place for couples who want to get married. This article offers the role of premarital guidance as a new approach to Christian family harmony, specifically the introduction of Christian values ​​regarding marriage and experiencing the implementation of premarital teaching in Christian families at Bethel Church of Indonesia Tabgha Batam. This approach provides an understanding as well as explains the tasks and challenges of couples who are planning to get married and also encourages them to prepare themselves optimally to carry out their family as husband and wife in the future. This research was conducted in natural conditions (natural setting). Specifically discussing the role of premarital guidance in realizing family harmony. The role of premarital guidance in realizing family harmony at the Bethel Indonesia Tabgha Batam Church is very evident. This method can be said to have succeeded in realizing them that a marriage becomes a strong marriage, if both the bride and groom make careful and thorough preparations. Careful means both have the ability to anticipate various things that will arise from the marriage. Mature in the sense that both of them are willing to work together in growing enthusiasm, comfortable, willing and without coercion at all in entering the gates of Christian marriage.